The gastronomic product of Łódź hotels - Kozłowska, Anna (Turyzm/Tourism, 2019)
Restaurants and other facilities providing catering services are an important part of hotels, can be their flagship product or make them unique. The obligation to provide restaurant services was imposed by the Ordinance of the Minister of Economy and Labour of 19th August 2004, concerning hotel and other facilities where hotel services are provided. Despite the dynamic development of gastronomy in the 21st century, running catering facilities in hotels is often an obligation which does not bring additional income. The aim of the research is to present the gastronomic product in Lodz hotels, understood as all the services related to gastronomy that are provided. The analysis was conducted with respect to the brand of the facilities, references to local cuisine and the availability of hotel gastronomy to potential guests. The work also presents factors that may facilitate access to hotel gastronomy, breaking the stereotype of ‘available only for hotel guests’, as well as the advantages of using the hotel's gastronomic product in a proper way.